Personal Branding Pustakawan Sekolah Melalui Ajang GTK Berprestasi - Andina, Syifa; Zulaikha, Sri Rohyanti (Nur Science Institute, 2025)
This study aims to explore the influence of personal branding on the development of school librarians' professionalism through participation in the Teacher and Education Personnel (GTK) Berprestasi event. The method used in this study is a qualitative approach with literature analysis. This study collected data from various sources, including journals, books, and guidelines related to the Teacher and Education Personnel (GTK) Berprestasi event held by the Regional Education Office. Through thematic analysis, this study identified personal branding strategies that librarians can apply to increase their visibility and credibility. The results of the study indicate that the Teacher and Education Personnel (GTK) Berprestasi event serves as an effective platform for librarians to showcase their achievements and innovations. Participation in this event not only increases recognition of librarians' contributions but also expands their professional networks and strengthens their reputation in the community. Thus, this study concludes that effective personal branding development through the Teacher and Education Personnel (GTK) Berprestasi event can encourage increased professionalism and quality of school libraries.